Produção e qualidade pós-colheita de couve-flor em função de doses de potássio em cobertura - Godoy, Amanda Regina (2012)
This paper aims to evaluate the effect of rates of potassium in top dressing on yield and quality of cauliflower of the cultivar Teresópolis Gigante. The experiment was conducted at São Manuel Experimental Farm of UNESP/FCA, from April to August 2006. Five treatments (0; 50; 100; 150 and 200 kg ha-1 of K2O in top dressing) were evaluated with a randomized complete block design involving five replications and ten plants per plot. At the harvest, evaluations were made in the number of leaves per plant, curd diameter and average weight; and the postharvest characteristics evaluated were pH, titratable acidity, level of soluble solids, reducing sugars, vitamin C and potassium content. It was observed that the rates of potassium did not influence these characteristics, showing that the application of this nutrient in top dressing is probably not necessary when fertilization occurs at planting, despite the existing recommendations for the crop.